Snapshot Impact of COVID-19 on Mental Wellness in Nonphysician Otolaryngology Health Care Workers: A National Study. Issue 3 (August 2020) - Prasad, Aman; Civantos, Alyssa M.; Byrnes, Yasmeen; Chorath, Kevin; Poonia, Seerat; Chang, Changgee; Graboyes, Evan M.; Bur, Andrés M.; Thakkar, Punam; Deng, Jie; Seth, Rahul; Trosman, Samuel; et al.
Objective: Nonphysician health care workers are involved in high-risk patient care during the COVID-19 pandemic, placing them at high risk of mental health burden. The mental health impact of COVID-19 in this crucial population has not been studied thus far. Thus, the objective of this study is to assess the psychosocial well-being of these providers. Study Design: National cross-sectional online survey (no control group). Setting: Academic otolaryngology programs in the United States. Subjects and Methods: We distributed a survey to nonphysician health care workers in otolaryngology departments across the United States. The survey incorporated a variety of validated mental health assessment tools to measure participant burnout (Mini-Z assessment), anxiety (Generalized Anxiety Disorder–7), distress (Impact of Event Scale), and depression (Patient Health Questionnaire–2). Multivariable logistic regression analysis was performed to determine predictive factors associated with these mental health outcomes. Results: We received 347 survey responses: 248 (71.5%) nurses, 63 (18.2%) administrative staff, and 36 (10.4%) advanced practice providers. A total of 104 (30.0%) respondents reported symptoms of burnout; 241 (69.5%), symptoms of anxiety; 292 (84.1%), symptoms of at least mild distress; and 79 (22.8%), symptoms of depression. Upon further analysis, development of these symptoms was associated with factors such as occupation, practice setting, and case load. Conclusion: Frontline otolaryngology health care providers exhibit high rates of mental health complications, particularly anxiety and distress, in the wake of COVID-19. Adequate support systems must be put into place to address these issues.